KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA - Siwi, Adiratna Sekar (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Chronic kidney failure is a decrease in kidney function and chronic nature which may require replacement irreversible kidney dialysis therapy accompanied on the final stages of kidney failure. Therapy hemodialysis is a replacement therapy for removing the remains of the metabolism of the human blood circulation that will affect the quality of life. Factors that affect the quality of life, among others, age, gender, occupation, education, frequency of Hemodilaisa, long Hemodialisa, chronic renal failure stage, and relationship with the nurse. This research aims to know the description of the quality of life in chronic renal failure patients at the Hemodialysis Room Wijaya Kusuma Hospital Purwokerto.Â The typeÂ of this research is quantitative descriptive research with methods cross-sectional. Sampling using accidental sampling. The respondents in this study as many as 94 patients. Instrument in this study using questionnaire KDQOL SF 1.3 to measure the quality of life of patients with kidney failure. Quality of life in chronic renal failure patients undergoing hemodialysis therapy at the Wijaya Kusuma Hospital Purwokerto is largely good in quality of life (73.4%). Mostly on the age group 45-60 years as many as 39 quality of life patients either (41.5%), mostly male-sex that is as much as 41 patients living quality good (43.6%), educational background of patients most life is good-quality secondary education group 35 patients (37.2%). The work of most of the patients already not working with a total of 44 patients (46.8%), quality of life is good and the length of time patients undergoing therapy at the most hemodialysis time is under 12 months with quality of life good as much as 26 patients (27.7%).